Cellular and humoral events during homograft reaction in diffusion chambers - Capalbo, Elmo Eduardo (International Atomic Energy Agency; Austria, 1968)
Fil: Capalbo, Elmo Eduardo Comisión Nacional de Energía Atómica; Argentina